Who Cares about social image? - Jana Friedrichsen; Dirk Engelmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper experimentally investigates how concerns for social approval relate to intrinsic motivations to purchase ethically. Participants state their willingness-to-pay for both a fair trade and a conventional chocolate bar in private or publicly. A standard model of social image predicts that all increase their fair trade premium when facing an audience. We find that the premium is higher in public than in private only for participants who preferred a conventional over a fair trade chocolatebar in a pre-lab choice. This is captured by a generalized model where intrinsic preferences and the concern for social approval are negatively correlated.
Keywords: D03; C91; D12; 330; image concerns; ethical consumption; fair trade; social approval; crowding out; experiments